Kontribusi Kekuatan Otot Lengan Terhadap Kecepatan Renang Gaya Bebas Pada Atlet Renang Spc Swimming Club - Romadan, Perdian Fajar; Lismana, Oetari; Putra, Dwingki Marta (Educative Sportive, 2024)
This study aims to determine the contribution of arm muscle strength to freestyle swimming speed in SPC Swimming CLUB swimming athletes. This research method is Correlation research. The research sample totalled 20 people. The instruments used in this study were the Pull Up Test and 50 metre swimming speed. Where the results of the study there is a contribution of arm muscle strength to swimming speed in SPC Swimming CLUB athletes, that arm muscle strength to swimming speed in SPC Swimming club athletes is 89.62% which means it contributes to swimming speed.